A survey of oral health in a Sudanese population - Khalifa Nadia; Allen Patrick F; Abu-bakr Neamat H; Abdel-Rahman Manar E; Abdelghafar Khalda O (BMC, 2012)
Abstract Background We aimed to assess the oral health status and risk factors for dental caries and periodontal disease among Sudanese adults resident in Khartoum State. To date, this information was not available to health policy planners in Sudan. Methods A descriptive population-based survey of Sudanese adults aged ≥ 16 years was conducted. After stratified sampling, 1,888 adult patients from public dental hospitals and dental health centres scattered across Khartoum State, including different ethnic groups present in Sudan, were examined in 2009-10. Data were collected using patient interviews and clinical examinations. Dental status was recorded using the DMFT index, community periodontal index (CPI), and a validated tooth wear index. Results Caries prevalence was high, with 87.7% of teeth examined having untreated decay. Periodontal disease increased in extent and severity with age. For 25.8% of adults, tooth wear was mild; 8.7% had moderate and 1% severe toothwear. Multivariate analysis revealed that decay was less prevalent in older age groups but more prevalent in southern tribes and frequent problem based attenders; western tribes and people with dry mouths who presented with less than18 sound, untreated natural teeth (SUNT). Older age groups were more likely to present with tooth wear; increasing age and gender were associated with having periodontal pocketing ≥ 4 mm. Conclusions The prevalence of untreated caries and periodontal disease was high in this population. There appear to be some barriers to restorative dental care, with frequent use of dental extractions to treat caries and limited use of restorative dentistry. Implementation of population-based strategies tailored to the circumstances of Sudanese population is important to improve oral health status in Sudan.